Potencial micorrícico de bosques del Chaco Árido con distintos niveles de degradación por uso ganadero-forestal - Sagadin, Monica Beatriz; Cavallero, Laura; Alaggia, Francisco Guillermo; Lopez Lauenstein, Diego; Melchiorre, Mariana; Lopez, Dardo Ruben; Muñoz, Nacira Belen (Universidad Nacional de Hurlingham, 2022)
Poster